Stimulation of Students’ Leadership Abilities Through Musical Project Activity - Kirliauskienė, Rasa; Stakauskaitė, Lijana (Pedagogika, 2016)
For a long time leadership has been considered as the key factor significantly influencing the success of the organization; however, its role in the school learning has been especially emphasized recently. Abilities and roles of leaders of education system, i.e. teachers, mentors, are analysed in the most of sources of literature; however, there are few discussions about education of leadership of students. The current musical educational project, as an instrument of musical educational technology encouraging the skills of students’ leadership, was chosen due to the lack of sufficient research showing the skills of students’ leadership. The objective of the research: the encouragement of the skills of students’ leadership using the musical project-based activity during the informal education process. The aim of the research: to reveal the encouragement possibilities of students’ leadership skills while executing the educational musical project. The objectives of the research: 1. To find out the features of educational project as an instrument of musical educational technology and to implement the educational project. 2. Following the material of the research, to find out the efficiency of educational project, as encouragement of the skills of students’ leadership. The methods of the research: the analysis of scientific literature and documents, project of education, survey data analysis. The background of the research and the methodology. The musical project was developed in order to reveal the encouragement possibilities of students’ leadership skills and to identify the features of educational project as an instrument of musical educational technology. The pop music project “Rudeninė karuselė” is one of forms of education of self-expression, creativity, communication and cooperation of children and young people. It aims for education of children and young people in the creative arts, for the nurturance of the traditions of singing, for the popularisation of artistic expression of singers, for the selection of best soloists and vocal ensembles, and for the promotion of creation and performance of new Lithuanian songs for children. Conclusions. The results of the research revealed that participation in informal musical education is caused by good feeling, manifestation of oneself to the public, the demand for education. Musical project-based activity is an effective instrument for encouraging of students’ leadership skills during informal musical education process. It was found out during the research that the participation in musical projects promotes the leadership skills such as responsibility, striving for win, self confidence, perseverance, cooperation, enthusiasm. The leadership, planning and other educational leadership skill can be developed during the participation in musical projects. While discussing the environment of participants in order to enhance the leadership, mentors urge to take the leader’s role and responsibility; they appreciate efforts of children striving for leadership; the leadership is being promoted while organizing the fun activity, as well. The research showed that the need of attention, the achievement of goal, perseverance and communication are being promoted during the participation in musical events.